Proposed Seremban Civic Centre / Ismail Suleiman - Suleiman, Ismail (1985)
For sometime the Town Council of Seremban had felt the need for a social centre and focus and were considering building a sports and cultural hall in the town centre. To construct the public assembly facility most needed by a community is perhaps the best formula for a successful project, but deciding what to build often proves more difficult. All too often projects are launched on the basis of personnel desires, competition with other cities, community pride, political pressures, bussiness influences, and a score of similar reasons. From such beginnings have come many of those buildings that will remain a tax burden on their towns for many years to come. Misconceptions or misinterpretations of community requirements or other demands often constitute much of the problem. Greater attention to advance planning should result in facilities that not only serve their communities better but should also provide greater revenues and lower operating costs (which also include expenditure and maintainance).Thus proper studies must be carried out in determining the feasibility of the project, its site location, cost limitations of the project and lastly the planning or the design stage of the building itself.